Manejo terapéutico del aborto en el Hospital Julius Dopfner de Zamora Chinchipe. - Becerra Guamán, Klever Ramón (2017)
Abortion is an urgent health issue in the communities, in the face of this public health problem, and with it being one of the most common medical emergencies in a day by day basis, it is of utmost importance to state the adequate use of protocols and guidelines stablished by the MSP. The experts committee for the selection and usage of essential medications decided that the effectiveness of misoprostol is similar to that of surgical evacuation and it may be safer and less expensive in some scenarios. The objectives that were stablished in this study were. To stablish the frequency of presentation of miscarriages in JULIUS DOEPFNER hospital in the province of Zamora chinchipe during the period January-June 2016. To determine the types of miscarriage that presented under the 12 weeks of gestation in the JULIUS DOEPFNER hospital during the period January-June 2016. To stablish the usage, frequency and efficiency of misoprostol as first line treatment in early miscarriages. The study type was: analytical, retrospective and transversal; the universe was the women that attended the emergency services with symptoms and signs compatible with abortion prior to 12 weeks of pregnancy. Out of the cases of miscarriages that were presented in JULIUS DOEPFNER hospital during the period January-June 2016, 91% correspond to confirmed miscarriages, and 9% to miscarriage menaces, out of 61 confirmed miscarriages, 81% correspond to incomplete spontaneous miscarriage prior to 12 weeks of pregnancy, and 2% to differed miscarriages prior to 12 weeks of pregnancy. keywords: Abortion, Abortion spontaneous incomplete, MSP protocol, Misoprostol, Women 12 weeks gestation pregnancy.